2022
DOI: 10.1021/acsami.2c16857
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement in Site-Specific Delivery of Chloramphenicol Using Bacterially Sensitive Microparticle Loaded Into Dissolving Microneedle: Potential For Enhanced Effectiveness Treatment of Cellulitis

Abstract: One of the biggest challenges in infectious disease treatment is the existence of bacterial infections in underskin wound tissue, such as cellulitis. Compared to other treatments, it is harder for antibacterial drugs to penetrate the physical barrier on the affected skin with a nonspecific target, making conventional therapy for cellulitis infection more difficult and considered. In this novel research, we pioneer a combined strategy of dissolving microneedles (MNs) and bacteria-sensitive microparticles (MPs) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 55 publications
1
4
0
Order By: Relevance
“…The results of the antibacterial inhibition test from the liquid hand washing soap sample obtained the average diameter of the inhibition zone at each concentration; namely a 3% concentration of 8.27 mm, 6% concentration of 10.55 mm, and 9% concentration of 11.16 mm and the soap base control has no inhibition zone. This is in line with research conducted by Utami (2020), which states that the greater the concentration in each formulation, the greater the inhibition of the bacteria (Maramis & Asri, 2022;Mulyani & Hendick, 2022;Mudjahid et al, 2022).…”
Section: Resultssupporting
confidence: 89%
See 2 more Smart Citations
“…The results of the antibacterial inhibition test from the liquid hand washing soap sample obtained the average diameter of the inhibition zone at each concentration; namely a 3% concentration of 8.27 mm, 6% concentration of 10.55 mm, and 9% concentration of 11.16 mm and the soap base control has no inhibition zone. This is in line with research conducted by Utami (2020), which states that the greater the concentration in each formulation, the greater the inhibition of the bacteria (Maramis & Asri, 2022;Mulyani & Hendick, 2022;Mudjahid et al, 2022).…”
Section: Resultssupporting
confidence: 89%
“…Damage to the bacterial cell wall will react with the alcohol group of the flavonoid compound, causing the absorption of these compounds into the nucleus of the bacterial cell. Then the DNA contained in the nucleus of the bacterial cell will react with the flavonoid compound through the difference in polarity between the alcohol groups and the lipids that make up the DNA, causing the nucleus of the bacterial cell to lysis (Nurhayati et al, 2020;Mudjahid et al, 2022;Utami, 2020).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The results suggested that Dox MS exhibited excellent lipase response performance, which was consistent with previous reports. [ 25 ] Second, we constructed an in vitro model simulating a wound barrier to examine the penetration of microneedles and the effect on drug delivery. The results demonstrated that microneedles can effectively pierce the physical barrier of the wound and deliver the drug uniformly to the interior of the biofilms.…”
Section: Discussionmentioning
confidence: 99%
“…Mechanically robust dissolving microneedle (DMN) patch can penetrate the compact EPS barrier of biofilms to deliver antibacterial agents effectively, thus showing great promise for eliminating biofilms. Herein, for the first time, we developed a DMN patch composed of a supramolecular photosensitizer (SP) for enhanced penetration and photodynamic elimination of bacterial biofilms (Scheme ). Tetra­(4-pyridyl)-porphine (TPyP), a commonly used porphyrin derivative, was successfully included into sulfobutylether-β-cyclodextrin (SCD) through supramolecular interactions.…”
Section: Introductionmentioning
confidence: 99%